P4.61 Sexual identity, attraction and experience in britain: the implications of using different dimensions of sexual orientation to estimate the size of sexual minority populations. (8th July 2017) - Ch, Mercer; Geary, R; Tanton, C; Erens, B; Clifton, S; Kr, Mitchell; Sonnenberg, P
Abstract : Introduction: Sexual orientation encompasses three dimensions: sexual identity, attraction and behaviour. Many health and policy surveys and inequality monitoring activities collect data only on identity, while STI risk is primarily driven by behaviour. We present estimates of all three dimensions and examine the extent of their overlap, for men and women, and consider the implications of using the different criteria to estimate the size of sexual minority populations in Britain. Methods: Descriptive analyses of data from Britain's third National Survey of Sexual Attitudes and Lifestyles, a probability survey (15 162 people aged 16–74 years) undertaken 2010–2012 using a computer-assisted personal- and self-interviewing (CAPI/CASI). A standard question was used to define sexual identity (CAPI). Participants were also asked to describe their sexual attraction according to a scale ranging from exclusively opposite-sex to exclusively same-sex (CAPI). Same-sex sex was defined as ever having had sex (including genital contact) with someone of the same sex (CASI). Results: A lesbian, gay or bisexual (LGB) identity was reported by 2.5% of men and 2.4% of women, whilst 6.5% of men and 11.5% of women reported any same-sex attraction, and 5.5% of men and 6.1% of women reported ever experience of same-sex sex. This equates to approximately 5 73 000 men and 5 59 000 women in Britain currently self-identifying as LGB, less than half the number who are estimated to have ever had same-sex sex: 1, 262, 000 men and 1, 422, 000 women. Of those reporting having same-sex sex in the past 5 years, 28% of men and 45% of women identified as heterosexual. Conclusions: Substantial incongruity exists between the three measures of sexual orientation on an individual level, particularly for women. The size of sexual minority populations will depend on the dimension of sexual orientation applied, the choice of which depends on context and purpose. Regardless, the decision to use a particular dimension should be made explicitly, with a clear rationale, and with awareness of the limitations of each.